Azerbaijan : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
Contents include: Real sector developments: output trends; sectoral developments; and income, wages, and prices. Public finances; fiscal balance; revenue developments; expenditure developments; social safety net. Financial sector developments; monetary and exchange rate developments; the use of monetary instruments; and commercial banking sector developments and bank supervision. External sector developments; current accounts: capital account and external debt; and trade payments, and exchange system. Structural issues: privatization; price liberalization; structure of government; and other structural issues. Statistical tables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet